Synthesis of (Cu,Mn,Co)3O4 Spinel: Effects of Citrate-to-Nitrate Ratio on Its Homogeneity and Electrical Properties - Joelle C. W. Mah; Isyraf Aznam; Andanastuti Muchtar; Mahendra Rao Somalu; Jarot Raharjo (Energies, 2023)
The (Cu,Mn,Co)3O4 (CMC) spinel layer is useful in inhibiting Cr vaporization that deteriorates the solid oxide fuel cell performance. The effectiveness of the spinel layer in suppressing volatile Cr species from the metallic interconnects is strongly dependent on layer density, which is influenced by particle size distributions and agglomerations of the spinel powders. Considering that the material properties were influenced by the synthesizing conditions, this study elucidated the influences of citric acid (fuel) on the structure, morphology, and electrical properties of sol–gel derived CMC spinel powders. Dual-phase CMC spinel powders, consisting of cubic CuMnCoO and tetragonal Mn2CoO4, were successfully synthesized at citrate-to-nitrate (CA/MN) ratios of 0.8, 1.0, and 1.2. An undesired CuCo2O4 phase was observed in spinel powders synthesized at a low CA/MN ratio of 0.5. The CA/MN ratio has influenced not only the phase formation of CMC spinel, but also the particle size distributions. The CA/MN ratio of 1.0 yielded the finest CMC spinel with the least agglomerates, which then produced the highest electrical conductivity of 116 Scm−1. Therefore, the CA/MN ratio of 1.0 was recommended for the synthesis of CMC spinel, which can be used in fabricating the protective coating of solid oxide fuel cell interconnects.